Analisis Financial Distress Dalam Menilai Kinerja Perusahaan Dengan Model Altman Z-Score Pada Perusahaan Property & Real Estate Yang Terdaftar Di BEI Periode 2020-2022 - Natrion; Chagita Nanda Alifa (Mulia Pratama, 2023)
This study aims to analyze financial distress in assessing company performance using the altman z-score model for property & real estate companies listed on the Indonesia Stock Exchange. This study uses secondary, The data obtained by using a purposive sampling technique, namely as many as 39 companies with 93 samples. The data analysis method used is descriptive statistical analysis and logistic regression analysis. The results of this study indicate that the Market Value of Equity to Book Value of Debt has an effect on Financial Distress. Meanwhile, Working Capital to Total Assets, Retained Earning to Total Assets, Earning Before Interest and Tax to Total Assets, and Sales to Total Assets have no effect on Financial Distress. Based on the hypothesis simultaneously all the Altman Z-Score variables have a significant effect on the Financial Distress variable.